Novel methylation specific real-time PCR test for the diagnosis of Klinefelter syndrome - Mehta, Akanksha (Medknow Publications & Media Pvt Ltd, 2014)
The aim of this study was to design a molecular assay for the diagnosis of Klinefelter syndrome (KS), based on the detection of supernumerary X-chromosomes (X-chs). DNA was extracted from peripheral blood samples of twenty-six 47,XXY males; two 46,XY/47,XXY males; twenty-two 46,XY males; and 15 females; and deaminated. Methylation-specific quantitative polymerase chain reaction (MS-qPCR) was performed using primers for unmethylated and methylated copies of the X-ch inactive-specific transcript (XIST-U and XIST-M) gene. X-ch disomy was determined on the basis of XIST methylation status. Degree of mosaicism in the 46,XY/47,XXY males was compared with karyotype and fluorescent in situ hybridization (FISH) results. Data analysis was performed using the Roche® LightCycler software V. 3.5.3., including determination of crossing points (CPs) by fit-point analysis and melting curve analysis. X-ch disomy was detected in all female controls and KS patients; male controls expressed XIST-M only. CPs ranged from 29.5 to 32.5 (standard deviation (s.d.) 0.8) for XIST-U and from 29 to 31 (s.d. 0.6) for XIST-M. Limit of detection of mosaicism was 1%. Based on XIST-U/XIST-M ratios for the two 47,XXY/46,XY patients, the calculated degree of mosaicism (1.8% and 17.8%) was comparable to FISH results (2.3% and 15%, respectively). Turnaround time from DNA deamination to final data analysis was under 9 h. We conclude that MS-qPCR is a sensitive, specific and rapid test for the detection of X-ch disomy, with applicability for the screening and diagnosis of KS, even in the setting of low grade 47,XXY/46,XY mosaicism.